Cơ chế tương tác và xác định các thông số tương tác đất với cốt phục vụ tính toán ổn định công trình đất có cốt - Hùng, Vũ Đình; Duân, Khổng Trung (Vietnam Journal of Earth Sciences, 2012)
summaryStudy on interaction mechanism and determination of soil-reinforced material interaction parameters for stabilization analysis of reinforced soil worksDue to high economical and technical efficiency Geotextile reinforced soil technology is presently a widely applicable solution in construction of weak earth works, slope stability structures and in preventionof earthquake acceleration. However, there were difficulties in applying this technology in Vietnam as lack of a guidance on required parameters, their determination methods and their utilization in design.This paper presents major mechanisms of interaction between soil and reinforced geotextiles, then figure out required parameters and the way to determine them. Besides, the paper also introduces results of several experiments determining those parameters and comments to have better understanding on them, their selection and/or  determination and their application for a appropriate design analysis.